*This preview shows
page 1. Sign up to
view the full content.*

**Unformatted text preview: **2 3.55: a) With 0 = 45 , Eq. (3.27) is solved for v0 = gx 2 x- y . In this case, y = -0.9 m is the change in height. Substitution of numerical values gives v0 = 42.8 m/s . b) Using the above algebraic expression for v0 in Eq. (3.27) gives x y = x- 188 m (188.9 m) Using x = 116 m gives y = 44.1 m above the initial height, or 45.0 m above the ground, which is 42.0 m above the fence.
2 ...

View Full
Document